Dampak Pendapatan Asli Daerah Dimediasi Pertumbuhan Ekonomi Terhadap Belanja Modal Provinsi Aceh - Zainuddin; Mufadhdhal, Muhammad Farras; T. Makmur (Lembaga Otonom Lembaga Informasi dan Riset Indonesia (KITA INFO dan RISET) - Lembaga KITA, 2024)
This study aims to examine the influence of Regional Own-Source Revenue (PAD) on Capital Expenditure (BM) and analyze the mediating role of Economic Growth (PE) in this relationship. Furthermore, this research investigates the impact of PAD, mediated by PE, on BM in Aceh Province during the period of 2015–2023. The data used in this study are secondary data sourced from www.bps.go.id and www.djpk.kemenkeu.go.id. Data analysis was performed using the Least Squares Method and the Sobel Test. The results show that PAD has a significant effect on BM, and PE effectively mediates this relationship. The Sobel Test indicates that PE strengthens the influence of PAD on BM in Aceh Province. Therefore, PAD will have a stronger impact on BM when accompanied by an increase in PE.